PENGEMBANGAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE BERBASIS INQUIRY LEARNING PADA MATERI PENCEMARAN AIR DALAM MENUMBUHKAN KEMAMPUAN BERPIKIR KREATIF SISWA SMP - Tri Utami Setianingrum -; Lulu Tunjung Biru; Adi Nestadi (UNIB Press, 2023)
Based on the results of interviews conducted with several schools in Serang City, the use of instructional media commonly used by teachers tends to be less attractive and less varied. Learning media that are less attractive can be overcome by developing articulate storyline learning media and can foster the creative thinking skills of junior high school students. This development research aims to determine the efficiency level of inquiry learning-based articulate storyline learning media on water pollution in cultivating creative thinking skills for seventh grade junior high school students. The research method used in this research is Research and Development, in accordance with the needs of researchers by being limited to the dissemination stage until limited trials of the product being developed. This study used instruments in the form of validation questionnaire sheets and also student response questionnaires to determine the efficiency level of articulate storyline learning media. Data analysis used is qualitative data and quantitative data. The results of this study indicate that the level of efficiency in developing inquiry learning-based articulate storyline learning media on water pollution material is assessed by validating material experts to get a percentage of 84% and is included in the very valid category, media expert validation gets a percentage value of 79% and is included in the valid category, and practitioner expert validation gets a percentage of 83% and is included in the very valid category. As well as the results of student responses also show a percentage value of 91.75% and are included in the very good category, so the use of articulate storyline learning media based on inquiry learning on water pollution material is very efficient and practical for use by students in the learning process.